The Influence of Sales And Operational Costs on Net Income in Cirebon Printing Companies - Rihfenti Ernayani; Rusydi Fauzan; Muhammad Yusuf; Jemi Pabisangan Tahirs (Al-Kharaj: Journal of Islamic Economic and Business, 2022)
he purpose of this study was to determine the effect of Sales, Operational Costs on net income. The population of this research is graphic printing in Cirebon. The sampling technique used is saturated sampling. The data collection method is descriptive. Data were analyzed using multiple linear-regressions. The results of the research on simultaneous tests are (1) Sales, operational costs have an effect on net income, (2) the partial test on sales variables has a significant effect on net income, (3) Operational costs have an effect on net income.